Deciphering the Molecular Basis of Mutated Binding Site Bromodomain-Ligand Complexes: Insights from Molecular Dynamics Simulations and Decoded Interaction Fingerprint Analysis - Riandono, Fransiscus Deddy (Universitas Wahid Hasyim Semarang, 2023)
This study aims to predict structural stability changes and to identify the molecular determinants of ligand-bromodomain complex interactions that undergo mutations in the ligand binding site (LBS) using computational chemistry methods. The stability changes of the complexes were investigated using Molecular Dynamics (MD) simulations during a 25 ns production run. The identification of molecular interaction determinants was performed by decoding the interaction fingerprint, utilizing the output of trajectory data of the MD simulations, which were converted into a series of pdb files along the time step. The system preparations were done using CHARMM-GUI. The MD simulations were carried out using the GROMACS program. Protein-ligand interaction fingerprints (PLIF) were identified using the PyPLIF-HIPPOS program. This study successfully predicted the stability of both wild-type and mutated ligand-bromodomain complex structures, where the W81A mutation led to a decrease in complex stability. The key residues and non-hydrophobic interaction types responsible for the stabilities were identified as TRP81 aromatic edge-to-face, TYR139 aromatic edge-to-face, and TYR139 aromatic face-to-face.